Anagostic Interactions under Pressure: Attractive or Repulsive?1. Issue 8 (12th January 2015) - Scherer, Wolfgang; Dunbar, Andrew C.; Barquera‐Lozada, José E.; Schmitz, Dominik; Eickerling, Georg; Kratzert, Daniel; Stalke, Dietmar; Lanza, Arianna; Macchi, Piero; Casati, Nicola P. M.; Ebad‐Allah, Jihaan; Kuntscher, Christine
Abstract Square‐planar d8‐ML4 complexes might display subtle but noticeable local Lewis acidic sites in axial direction in the valence shell of the metal atom. These sites of local charge depletion provide the electronic prerequisites to establish weakly attractive 3c–2e M⋅⋅⋅HC agostic interactions, in contrast to earlier assumptions. Furthermore, we show that the use of the sign of the 1H NMR shifts as major criterion to classify M⋅⋅⋅HC interactions as attractive (agostic) or repulsive (anagostic) can be dubious. We therefore suggest a new characterization method to probe the response of these M⋅⋅⋅HC interactions under pressure by combined high pressure IR and diffraction studies.